2014
DOI: 10.1109/tcbb.2013.2296317
|View full text |Cite
|
Sign up to set email alerts
|

A Segmentation-Based Method to Extract Structural and Evolutionary Features for Protein Fold Recognition

Abstract: Abstract-Protein fold recognition (PFR) is considered as an important step towards the protein structure prediction problem. Despite all the efforts that have been made so far, finding an accurate and fast computational approach to solve the PFR still remains a challenging problem for bioinformatics and computational biology. In this study, we propose the concept of segmented-based feature extraction technique to provide local evolutionary information embedded in position specific scoring matrix (PSSM) and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 52 publications
(143 reference statements)
0
22
0
Order By: Relevance
“…It is also widely used in Bioinformatics and has outperformed other classifiers and obtained promising results for protein subcellular localization as well as similar studies (Dehzangi et al, 2014a(Dehzangi et al, , 2014bDong et al, 2009;Yang and Chen, 2011;Lyon et al, 2014). It aims to reduce the prediction error rate by finding the hyperplane that produces the largest margin based on the concept of support vector theory.…”
Section: Support Vector Machinementioning
confidence: 62%
See 3 more Smart Citations
“…It is also widely used in Bioinformatics and has outperformed other classifiers and obtained promising results for protein subcellular localization as well as similar studies (Dehzangi et al, 2014a(Dehzangi et al, , 2014bDong et al, 2009;Yang and Chen, 2011;Lyon et al, 2014). It aims to reduce the prediction error rate by finding the hyperplane that produces the largest margin based on the concept of support vector theory.…”
Section: Support Vector Machinementioning
confidence: 62%
“…In this study, we have used the logodds values to extract our features. It was shown in the literature that using these numbers produce similar output as using the probability values (Dehzangi et al, 2014a(Dehzangi et al, , 2014b. In the following subsections these four feature extraction methods will be explained in detail.…”
Section: Feature Extraction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also shown that by fusion of features the recognition rates can be improved [30]- [33]. For the latter task case, several classifiers have been developed or used including linear discriminant analysis [34], [35], Bayesian classifiers [2], Bayesian decision rule [36], k-nearest neighbor [25], [37], Hidden Markov model [38], [39], artificial neural network [40], [41], support vector machine (SVM) [6], [20], [21], [42], [43], and ensemble classifiers [20], [33], [41], [44], [45]. Among these classifiers, SVM (or SVM-based for ensemble strategy) classifier exhibits quite promising results [21], [26], [27].…”
mentioning
confidence: 99%